Cultural Transformation of Turats Education in Islamic Boarding Schools: Integration of Dormitories as a Space for Transforming Turats Learning in Improving Students' Understanding of the Yellow Book - Yaqin, Pais Ainul; Jazilurrahman, Jazilurrahman (Journal of Educational Management Research, 2025)
The transformation of Islamic boarding school education in the modern era presents challenges in maintaining the values of turats amidst increasingly dynamic social and cultural changes among students. This study aims to examine how dormitories act as spaces for cultural transformation, how the integration of learning creates the intellectual ethos of students, and how the process of turats transformation produces a contextual understanding of the holy book. This study uses a qualitative approach with a case study design, involving kiai, ustaz, and students as key informants through in-depth interviews, participatory observation, and documentation of learning activities. The results of the study show three main findings: (1) the integration between classes and dormitories fosters an intellectual ethos through a culture of scientific discussion and shared reflection; (2) the transformation of turats gives rise to a more contextual understanding of the yellow book to the social reality of students, with 78% of respondents showing a significant increase in text comprehension; and (3) dormitory life functions as a space for cultural transformation, where values such as discipline, responsibility, and togetherness are internalized through routine halaqah and mudzakarah activities. The contribution of this research lies in affirming the concept of dormitories as spaces for scientific and cultural transformation, which integrate cognitive, affective, and social dimensions within the Islamic boarding school education system. The practical implications of this research emphasize the importance of strengthening the synergy between formal and non-formal learning as a strategy to maintain the relevance of turats education amidst changing times, while simultaneously shaping students with scientific, adaptive, and reflective cultural characters.